2021
DOI: 10.1080/17453674.2021.1979793
|View full text |Cite|
|
Sign up to set email alerts
|

Arthroscopic partial meniscectomy: did it ever work?

Abstract: Arthroscopic partial meniscectomy (APM) is one the most common orthopedic surgical procedures. The most common indication for APM is a degenerative meniscal tear (DMT). High-quality evidence suggests that APM does not provide meaningful benefits in patients with DMTs and may even be harmful in the longer term. This narrative review focuses on a fundamental question: considering the history and large number of these surgeries, has APM ever actually worked in patients with DMT? A truly effective treatment needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…10,14,21,23,25-27 The rationale for APM is ultimately to treat knee pain, but research on the pathoanatomy of meniscus tears in degenerative knees does not support its biological role nor does compelling evidence demonstrating its efficacy in relieving pain exist. 28…”
Section: Discussionmentioning
confidence: 99%
“…10,14,21,23,25-27 The rationale for APM is ultimately to treat knee pain, but research on the pathoanatomy of meniscus tears in degenerative knees does not support its biological role nor does compelling evidence demonstrating its efficacy in relieving pain exist. 28…”
Section: Discussionmentioning
confidence: 99%
“…A DMT is different from an acute meniscal injury associated with acute trauma or sports injury. DMTs are usually considered atraumatic and often present spontaneously or after low-energy injuries (5).…”
Section: Introductionmentioning
confidence: 99%
“…Given this scientific evidence, meniscal repair is recommended, especially in younger individuals. [9][10][11] The success or failure of meniscal repair is highly influenced by factors such as tear location, pattern, chronicity, size, and extent; repair technique; and patient age and habits. 12,13 A recent meta-analysis by Xu and Zhao 14 concluded that better long-term outcomes are obtained after meniscal repair than after meniscectomy, but the reoperation rate is on the higher side.…”
mentioning
confidence: 99%
“…Given this scientific evidence, meniscal repair is recommended, especially in younger individuals. 9 , 10 , 11 …”
mentioning
confidence: 99%